Intraoperative left ventricular perforation with false aneurysm formation. - Sharratt, G P (1976)
Two cases of perforation of the left ventricle during mitral valve replacement are described. In the first case there was perforation at the site of papillary muscle excision and this was recognized and successfully treated. However, a true ventricular aneurysm developed at the repair site. One month after operation rupture of the left ventricle occurred at a second and separate site on the posterior aspect of the atrioventricular ring. This resulted in a false aneurysm which produced a pansystolic murmur mimicking mitral regurgitation. Both the true and the false aneurysm were successfully repaired. In the second case perforation occurred on the posterior aspect of the atrioventricular ring and was successfully repaired. However, a false ventricular aneurysm developed and ruptured into the left atrium producing severe, but silent, mitral regurgitation. This was recognized and successfully repaired. The implications of these cases are discussed.